Zen and the art of experiments: A note on preventive healthcare and the 2019 nobel prize in economics. (March 2020) - Das, Jishnu
Abstract: I discuss Banerjee, Duflo and Kremer's work on preventive healthcare in low-income countries. Their research in this field has changed the way that governments view cost-recovery for key preventive services, ranging from deworming to insecticide-treated bed-nets. Equally, their contributions also help us understand why markets likely under-produce preventive goods and how traditional economic thinking on externalities and subsidies may have to be reevaluated in the light of new experimental findings. Throughout, their research in this field typifies a deep commitment to learning from the setting that they are working in, as well as an unyielding dedication to improving the lives of the poor.